Analysis of Potential Drug-drug Interactions in Liver Cirrhosis Patients: Analisis Interaksi Obat-obat Potensial pada Pasien Sirosis Hati - Muti, Annisa Farida; Anindya, Chanica (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Patients with liver cirrhosis are at a high risk of drug interactions due to the use of multi-drug combination regimens. Objectives: This study analyzed potential drug-drug interactions in the liver cirrhosis patients at Gatot Soebroto Army Hospital, Jakarta in 2016. Material and Methods: This study employed an observational-cross sectional design with retrospective data collection of liver cirrhosis patients' medical records. The data of potential drug-drug interactions were identified using Drug Interaction Facts 2012 including the mechanism type, the severity and the onset of drug interactions. Results: As many as 88% of the liver cirrhosis patients experienced potential drug-drug interactions with a total of 35 cases. The highest proportions of the cases were found in the pharmacokinetic mechanism by approximately 25 cases (71.43%), minor severity comprising 29 cases (82.86%) and rapid onset by 19 cases (54.29%). The highest potential drug-drug interactions were furosemide-propranolol combination in 16 cases (45.72%). Conclusions: The high incidence of potential drug interactions in patients with liver cirrhosis requires high vigilance and close monitoring of all health professionals in achieving optimal therapeutic outcomes for the patients.